Why nature prevails over nurture in the making of the elite athlete - Georgiades, E.; Klissouras, V.; Baulch, J.; Wang, G.; Pitsiladis, Y. (BMC Genomics, 2017)
While the influence of nature (genes) and nurture (environment) on elite sporting performance remains difficult to precisely determine, the dismissal of either as a contributing factor to performance is unwarranted. It is accepted that a complex interaction of a combination of innumerable factors may mold a talented athlete into a champion. The prevailing view today is that understanding elite human performance will require the deciphering of two major sources of individual differences, genes and the environment. It is widely accepted that superior performers are endowed with a high genetic pot ential actualised through hard and prodigious effort. Heritability studies using the twin model have provided the basis to disentangle genetic and environmental factors that contribute to complex human traits and have paved the way to the detection of specific genes for elite sport performance. Yet, the heritability for most phenotypes essential to elite human performance is abov e 50% but below 100%, meaning that the environment is also important. Furthermore, individual differences can potentially also be explained not only by the impact of DNA sequence variation on biology and behaviour, but also by the effects of epigenetic changes which a ffect phenotype by modifying gene expression. Despite this complexity, the overwhelming and accumulating evidence, am ounted through experimental research spanning almost two centuries, tips the balance in favour of nature in the nature and nurture debate. In other words, truly elite-level athletes are built - but only from those born with innate ability. Why nature prevails over nurture in the making of the elite athlete.